STUDI EKSPERIMENTAL GASIFIKASI UPDRAFT SEKAM PADI DAN BATUBARA KUALITAS RENDAH BERKATALIS BENTONIT UNTUK PRODUKSI SYNGAS - Akhmad Syarief; Maidi Maidi (INFO-TEKNIK, 2019)
This Research aims to determine the amounts generated in the gas liquefactiongas process rice husk with lowcoal quality at temperatures at 500 ° C and to know the speed of the updraft gasification process rice husk and the low coal quality of Bentonite catalyst. This research uses updraft type gasification where the gas that can be generated from the gasifer section will flow into the flowmeter and will be accommodated in the urine bag. In this study obtained syngas results on the process of updraft rice husk gasification and low quality coal berkatalis bentonit. Most Syngas produce on sample A SP 200 gr: BB 0 gr: B 100 gr equal to 36,72L. In sample B 180gr: 20gram: 100gr at 31,47L. In the sample C 140gr: 60gr: 100gr At 27.3L. and the lowest volume of syngas produced on the D sample 100gr: 100gr: 100gr at 24.28L. The heating rate that can be used in the gas filtration process and the low quality coal catalyzed bentonite is obtained at the highest heating rate in sample A 200gr: 0gr: 100gr at 16.89 ° C / min. In sample B 180gr: 20gr: 100gr at 15.25 ° C / min. In sample C 140gram: 60 grams: 100 grams of 13.13 ° C / min The lowest heating rate was obtained in D 100gr: 100gr: 100gr at 11.26 ° C / min.